Analysis of Muslim Tourist Loyalty to Halal Gastronomic Tourism in Salatiga City - Andriyan Eka Sapta; Samani; Ida Nurhayati; Tutik Dwi Karyanti; Jusmi Amid (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2023)
The development of the City of Salatiga as a City of Gastronomy will increase local and community income through culinary tourism and increase the number of tourists visiting Salatiga. The concept of halal is currently used as a trend for developing the Islamic economy in Indonesia, starting from the emergence of halal products (food and beverages), halal cosmetics, halal fashion and halal tourism to lifestyle (halal tourism). The purpose of this study focuses on the loyalty of Muslim tourists and how they increase tourist loyalty in the city of Salatiga. This study will use a variant-based Structural Equation Model (SEM) with AMOS version 2.0. The population of this study will be focused on halal gastronomic tourists in Salatiga City, while the samples selected in this study must meet the requirements of tourists who have visited more than three times. The product quality variable (X1) positively and significantly affects the tourist satisfaction variable (Z). Product quality affects tourist satisfaction, so managers of gastronomic tourism are advised to improve food taste, food aroma, food durability, and physical appearance of food. The price variable (X2) positively and significantly affects the tourist satisfaction variable (Z). Prices affect tourist satisfaction, so tourism managers are advised to increase price affordability, price competitiveness, and suitability of prices with product quality. The tourist satisfaction variable (Z) positively and significantly affects tourist loyalty (Y). Tourist satisfaction affects tourist loyalty, so tourism managers are advised to increase the suitability of tourist expectations, intention to revisit, and willingness to recommend from tourists.